The influence of mathematical disposition and gender on the numerical ability of Grade X students of SMAN 1 Bae Kudus - Mutiara, Sela; Wahyuni, Fina Tri (Bulletin of Applied Mathematics and Mathematics Education, 2023)
The background of this study is the lack of mathematical disposition of students and different genders towards the numerical abilities of class X students of SMAN 1 Bae Kudus. This study aims to (1) determine the influence of mathematical disposition on the numerical abilities of class X students of SMAN 1 Bae Kudus; (2) knowing the influence of gender on the numerical ability of class X students of SMAN 1 Bae Kudus; (3) knowing the influence of mathematical and gender dispositions together on the numerical abilities of class X students of SMAN 1 Bae Kudus. The types and approaches of research used are correlation and quantitative. This study was conducted in class XE8 involving 32 students. The results showed that: (1) there was a positive and significant influence of mathematical disposition on numerical ability with a significant contribution of 0.000 < from 0.05, (2) there was no positive and significant influence of gender on numerical ability because the significance value was 0.975 > 0.05, and (3) there is a positive influence and the significant mathematical  disposition and gender together to the numerical ability of significance values of 0.000 < 0.05 and a percentage of 61.1%.